‘In God We Trust’: The role of religion in COVID-19 vaccinations in Dar es Salaam, Tanzania - Thomas J. Ndaluka; Ambrose T. Kessy; Chima E. Onuekwe (Journal of Public Health in Africa, 2025)
Background: After the outbreak of COVID-19, the World Health Organization (WHO) identified vaccines as one of the intervention mechanisms capable of controlling and preventing COVID-19 infections. However, the uptake of the vaccine was below the expectation, while the cause for such manifestation was unclear.